In situ genetic association for serotiny, a fire‐related trait, in Mediterranean maritime pine (Pinus pinaster). Issue 1 (10th September 2013) - Budde, Katharina B.; Heuertz, Myriam; Hernández‐Serrano, Ana; Pausas, Juli G.; Vendramin, Giovanni G.; Verdú, Miguel; González‐Martínez, Santiago C.
Summary: Wildfire is a major ecological driver of plant evolution. Understanding the genetic basis of plant adaptation to wildfire is crucial, because impending climate change will involve fire regime changes worldwide. We studied the molecular genetic basis of serotiny, a fire‐related trait, in Mediterranean maritime pine using association genetics. A single nucleotide polymorphism (SNP) set was used to identify genotype : phenotype associations in situ in an unstructured natural population of maritime pine (eastern Iberian Peninsula) under a mixed‐effects model framework. RR‐BLUP was used to build predictive models for serotiny in this region. Model prediction power outside the focal region was tested using independent range‐wide serotiny data. Seventeen SNPs were potentially associated with serotiny, explaining approximately 29% of the trait phenotypic variation in the eastern Iberian Peninsula. Similar prediction power was found for nearby geographical regions from the same maternal lineage, but not for other genetic lineages. Association genetics for ecologically relevant traits evaluated in situ is an attractive approach for forest trees provided that traits are under strong genetic control and populations are unstructured, with large phenotypic variability. This will help to extend the research focus to ecological keystone non‐model species in their natural environments, where polymorphisms acquired their adaptive value.